Absence of flexor carpi radialis identified during volar approach for fixation of distal radius fracture: a case report - Irie, Tomoyo (BMC Res Notes, 2018)
BACKGROUND: Volar locking plate fixation of distal radius fractures is commonly performed because of its good clinical outcomes. The flexor carpi radialis (FCR) approach is one of the most popular approaches to dissecting the volar side of the distal radius because of its simplicity and safety. We describe an extremely rare case of an absent FCR identified during a volar approach for fixation of a distal radius fracture. CASE PRESENTATION: A 59-year-old woman with distal radius fracture underwent surgery using the usual FCR approach and volar locking plate. We could not identify the absence of the FCR tendon preoperatively because of severe swelling of the distal forearm. At first, we wrongly identified the palmaris longus tendon as the FCR because it was the tendinous structure at the most radial location of the volar distal forearm. When we found the median nerve just radial to the palmaris longus tendon, we were then able to identify the anatomical abnormality in this case. To avoid iatrogenic neurovascular injuries, we changed the approach to the classic Henry’s approach. CONCLUSIONS: Although the FCR approach is commonly used for fixation of distal radius fractures because of its simplicity and safety, this is the first report of complete absence of the FCR during the commonly performed volar approach for fixation of a distal radius fracture, to our knowledge. Because the FCR is designated as a favorable landmark because of its superficially palpable location, strong and thick structure, and rare anatomical variations, there is the possibility of iatrogenic complications in cases of the absence of the FCR. We suggest that surgeons should have a detailed knowledge of the range of possible anomalies to complete the fixation of a distal radius fracture safely.